Pengenalan Literasi Keuangan Dasar Bagi Siswa Sd 050430 Desa Bunuraya Melalui Program KKN - Siti Aisyah; Azzura Nodian Nabawi; M. Dimas Dwi Utama; Siti Nurhalimah; Yusliani Yusliani (Pusat Riset dan Inovasi Nasional, 2026)
Financial literacy is a fundamental competency that should be developed from an early age to foster prudent financial behavior in the future. However, the level of financial literacy among elementary school students remains relatively low, particularly in rural areas. The Community Service Program (Kuliah Kerja Nyata/KKN) serves as a strategic platform for providing financial education to the community, including elementary school students. This study aims to describe the implementation of a basic financial literacy program for students of SD 050430 Bunuraya Village through the KKN program and to analyze its impact on students’ understanding of financial concepts. This study employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings indicate that the financial literacy program delivered through interactive learning media effectively improves students’ understanding of basic concepts such as saving, distinguishing between needs and wants, and simple management of pocket money. The program is expected to serve as an initial step in building early financial awareness and encouraging the involvement of schools and families in children’s financial education.